House Prices and Home Ownership: a Cohort Analysis - Renata Bottazzi; Thomas Crossley; Matthew Wakefield (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
England has very volatile house prices. We use pseudo-panel data spanning multiple house-price cycles over nearly forty years, to assess the extent to which house prices affect access to home ownership by age thirty, and whether differences in ownership rates persist. We find that ownership rates at age thirty have varied substantially, with this variation significantly related to prices. Measurement error problems - attenuation bias and other biases - complicate an analysis of the persistence of these differences in ownership. We use two methods - including one that develops the ideas of Deaton (1985) - to deal with this and find robust evidence that cohorts with low ownership rates at thirty close about 80% of the ownership gap by age forty.
Keywords: R21; R31; 330